Recursos hídricos transfronteiriços da bacia amazônica: estudo de caso sobre a atual gestão hídrica do Rio Amazonas na tríplice fronteira constituída pelas cidades-gêmeas de Tabatinga/BR e Letícia/CO e a Ilha de Santa Rosa/PE - Nascimento, Leonardo Leite (2016)
The use and conservation of transboundary water resources and border of the Amazon Basin requires the effective cooperation of all the countries that share this natural resource, in this case fresh water, essential to the life of their populations. Therefore, the signatory countries of the Amazon Cooperation Treaty (TCA) and today members of the Amazon Cooperation Treaty Organization (OTCA), where Brazil, Peru, Colombia, Venezuela, Bolivia, Ecuador and Guyana, shall endeavor to implement an integrated and sustainable management of shared international rivers, with effective adoption of bilateral and multilateral public policies in order to ensure the availability of fresh water for present and future generations. This work aims to examine the legal aspect in the light of the TCA and the rules of International Law, the current cross-border water management in the Amazon Basin, and the possibility and feasibility of implementing a joint management between the riparian countries. For their achievement we conducted a case study on the current water management of the world's largest river, the Amazon River, specifically its tributaries, rivers Marañón and Solimões in the triple border of Brazil, Peru and Colombia, on the stretch passing through twin cities Tabatinga/BR and Leticia/CO and the Santa Rosa Island/PE. The results show that, to obtain advances in the management of transboundary water resources, many steps should be met, starting with the understanding of the hydrological behavior of the Amazon River and the different social, political and economic conditions of each country involved. Thus, it must highlight the importance of institutional strengthening of OTCA and the necessary implementation of a transboundary basin committee for the tri-border countries, aiming to carry out the process of management and implementation of a local and regional water policy.